Fostering Innovative Entrepreneurial Design Students: Exploring the Relationship between Innovation Characteristics and Attitudes towards Entrepreneurship in South African Design Students. (1st December 2020) - Hendricks, Denver; Meyer, Marina
Abstract : Innovation and entrepreneurship have been increasingly recognized as drivers of socio-economic development. The term innovative entrepreneur is a relatively new one and could be necessary for economic growth during a challenging and changing global environment. Previous studies have found that limited job opportunities for architectural graduates has meant that many have changed careers while others have had to innovate to survive within the profession. Therefore, architects must transform and innovate to survive and so should our curriculum. Learning how to train these innovative entrepreneurs effectively is key. Innovation can be taught and result in improved entrepreneurial skills that develop better entrepreneurial competence. The challenge is for educators, researchers and policymakers to create curricula that will impact design students to foster innovative entrepreneurial graduates and lead to eventual growth in the economy. This article is the result of a study that explored and measured the characteristics and dynamics of an innovative entrepreneur in design students. The sample consisted of South African students from the architecture, interior, graphics and multimedia disciplines. The study is the first step in understanding what behaviours and attitudes are present in African innovative entrepreneurs. The findings suggest that there is a relationship between entrepreneurial attitudes and innovation characteristics and behaviours. These can be nurtured through a dynamic design curriculum and increase a design student's propensity to become a better designer within a thriving economy.